DEKONTRUKSI KONSEP SYARI’AH DI BIDANG HAM DALAM PEMIKIRAN ABDULLAH AN-NA’IM SERTA KONSTEKTUALISASINYA DALAM KONSTITUSI DI INDONESIA - Ahmad Khuzairi; Ibnu Jazari; Moh Muslim (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
Abstract Shariah are religious values that are expressed functionally and have a concrete meaning in directing life. Thus, the author would like to examine An-Naim’s views regarding the concept of sharih and human rights in the constitution in Indonesia. While the objectives of this thesis are: 1. To find out how the concepts of shariah and human rights according to An-na’im, 2. To find out about the implications of the An-na’im idea with the reality and development of sharia, especially for the life of modern society, especially in human rights issues in the constitution in Indonesia, 3. review the ides of renewal of An-Na’im in sharia deconstruction. This research method used descriptive qualitative. Thus, to collect the data, the researcher conducted the library research such as, books of Abdullah An-Na’im, journal, article, etc. According to An-Na’im the deconstruction of Syari'ah is needed interpretation, although syariah come from Allah its need to be re-interpretation. Keywords: Syariah, Deconstruction, Constitution